Expanding the purview of wellness indicators: validating a new measure that includes attitudes, behaviors, and perspectives - Carolyn E. Schwartz; Brian D. Stucky; Roland B. Stark (Health Psychology and Behavioral Medicine, 2021)
Objective The present study validated the DeltaQuest Wellness Measure (DQ Wellness), a new 15-item measure of wellness that spans relevant attitudes, behaviors, and perspectives. Design This cross-sectional web-based study recruited chronically-ill patients and/or caregivers (n = 3,961) and a nationally representative comparison group (n = 855). Main Outcome Measures The DQ Wellness assesses: a way of being in the world that involves seeing and embracing the good and expressing kindness toward others; engagement in one’s activities and self-care; downplaying negative thoughts that reduce one’s energy; and an ability to feel joy. Six widely used measures of physical and mental health, cognition, and psychological well-being enabled construct-validity comparisons. Item-response theory (IRT) methods evaluated reliability, factor structure, and differential item functioning (DIF) by gender. Results The DQ Wellness showed strong cross-sectional reliability (marginal reliability = 0.89) and fit a bifactor model (RMSEA = 0.063, CFI = 0.982, TLI = 0.983). The DQ Wellness general score demonstrated construct validity, convergent and divergent validity, unique variance, and known-groups validity, and minimal gender DIF. The study is limited to addressing cross-sectional reliability and validity, and response rates are not known due to the recruitment source. Conclusion The DQ Wellness is a relatively brief measure, taps novel content, and could be useful for observational or interventional studies.